Pelatihan Pemanfaatan Limbah Kelapa Sawit Menjadi Pupuk Semi Organik Bagi Siswa Jurusan Agribisnis Tanaman Perkebunan SMKN 1 Kuok - Nina Veronika; Fatmayati Fatmayati; Hanifah Khairiah; Nur Ama Deli; Antonius J Sihotang; Boris Kaido (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
In 2023, Riau's oil palm plantation area with cultivation status will reach 3.5 million hectares with palm oil production reaching 9.06 million tons (Ministry of Agriculture, 2023). This figure makes Riau Province the largest palm oil center province in Indonesia. As the area of oil palm plantations increases, palm oil waste will be produced consisting of empty bunches, fronds, shells and fiber. This palm oil waste can pollute the environment in water and soil and can also threaten biodiversity. One use of palm oil waste is compost. Organic fertilizer (compost) is the final and/or intermediate result of changes or decomposition of plant and animal parts and remains, for example cake, guano, bone meal, livestock waste and so on (Ege et al., 2018). The objectives of this PKM are given to students of SMKN 1 Kuok, namely 1) providing early knowledge about the use of palm oil waste, 2) understanding how to make compost from palm oil waste, and 3) socializing the facilities and infrastructure available at Kampar Polytechnic . Large land and facilities for making compost fertilizer are not available in the ATP department of SMKN 1 Kuok. So with this training in making compost fertilizer, we can overcome the problem of places and practicum areas that are not available at SMKN 1 Kuok.